Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Biro Administrasi Pimpinan Sekretariat Daerah Provinsi Jawa Timur - Azmi Abdul Rohman; Rudy Handoko; Endang Indartuti (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Human Resources play a vital role in determining the success of an organization. The existence of human resources with maximum performance can improve organizational performance. The research goals to analyze the partial and simultaneous impact of the work environment and work motivation on the performance of BAPSD East Java employees. The study uses a causal type. The sample population is 37 BAPSD East Java employees. Data collection through Questionnaires with SPSS analysis. The results of the study prove that the Work Environment has no significant correlation with Employee Performance, but Work Motivation has a significant correlation with Employee Performance. While simultaneously the Work Environment and Work Motivation have a significant correlation with Employee Performance.